2023
DOI: 10.1108/jhti-09-2022-0410
|View full text |Cite
|
Sign up to set email alerts
|

Traveling with special needs: investigating constraints and negotiation strategies for engaging in tourism activities

Abstract: PurposeThe aim of this study is to identify the travel constraints of people with special needs (PwSN) and the strategies used to overcome them. The article also intends to analyze the differences in travel constraints and negotiation strategies according to the type of disability and/or special need.Design/methodology/approachA qualitative study was conducted in which a sample of PwSN (people with disabilities – mobility, sensory and cognitive – seniors and people with food allergies) were interviewed in dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Managers of the different functional areas were then surveyed, and the findings revealed that "the most essential competencies for hospitality graduates to possess are in the soft category" (p.143) and they concluded that educational "programs should stress teaching hospitality students' soft competencies in favour of hard competencies" (p.131). These soft skills present unique opportunities to capture inter-personal, communication and diversity skills to enhance sustainable tourism indicators (Baum 2018) and hospitality practices that can help provide the missing link to achieve "socially sustainable tourism" (Devile et al, 2023;Habimana et al, 2023;Mínguez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Managers of the different functional areas were then surveyed, and the findings revealed that "the most essential competencies for hospitality graduates to possess are in the soft category" (p.143) and they concluded that educational "programs should stress teaching hospitality students' soft competencies in favour of hard competencies" (p.131). These soft skills present unique opportunities to capture inter-personal, communication and diversity skills to enhance sustainable tourism indicators (Baum 2018) and hospitality practices that can help provide the missing link to achieve "socially sustainable tourism" (Devile et al, 2023;Habimana et al, 2023;Mínguez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances "it has become increasingly important that students enter the workforce prepared to deal with diversity and multicultural issues" (Rivera & Lee, 2016, p. 156). Social skills are therefore critically important to support this end and comprise a key social element of sustainable tourism (Baum 2018;Carlisle et al, 2021;Devile et al, 2023;Habimana et al, 2023;Mooney et al, 2022;Mínguez et al, 2021).…”
Section: The Importance Of Social Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral strategies include schedule arrangements and skill development, while cognitive strategies involve balancing rewards and costs, increasing engagement, and how to deal with stress (Chen et al, 2020). Devile et al (2023) noted that the negotiation of travel constraints refers to the adoption of creative strategies that may overcome these constraints. Devile et al (2023) added that the analysis of travel constraints and negotiation strategies should be conducted concurrently due to their inescapable reciprocity.…”
Section: The Negotiating Strategies Of Travel Constraintsmentioning
confidence: 99%
“…Therefore, providing high-quality travel experiences to people with disabilities (PwDs) still poses significant difficulties (Rubio-Escuderos et al, 2021). Service providers and tourism agents must better understand travel constraints to offer more accessible tourism products and services and improve the tourism experience of PwDs (Devile et al, 2023;Załuska et al, 2022). Despite the importance of the participation of PwDs in tourism activities, in-depth studies from their own perspectives are limited (Rubio-Escuderos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%